Embroidered Metamaterial Antenna for Optimized Performance on Wearable Applications. Issue 21 (16th August 2018) - Gil, Ignacio; Seager, Rob; Fernández‐García, Raúl
Abstract : In this work, an embroidered metamaterial monopole antenna based on a split ring resonator electromagnetic bandgap shielding structure is designed, simulated, and tested. This work investigates the impact of different types of embroidering metamaterial patterns on the antenna performance, shielding effect in terms of human safety through specific absorption rate analysis and degree of material wearability, in comparison with the standard antenna topologies. The proposed antenna design presents a full compact embroidered metamaterial device manufactured in felt textile substrate and requires a 85 × 70 mm 2 area, operating at 2.45 GHz. On‐voxel analysis reveals that specific absorption standards are satisfied for both public and occupational sector with a significant safety margin whereas the antenna performance in terms of gain and directivity are significantly optimized with regard to standard wearable materials. Abstract : This work investigates the design of wearable embroidered metamaterial monopole antennas combined with a split ring resonator electromagnetic bandgap shielding, operating at 2.45 GHz. The study involves simulation and experimental antenna performance, shielding effect in terms of human safety through specific absorption rate analysis and degree of material wearability, in comparison with the standard antenna topologies.